Prevalencia y agentes patógenos asociados a infecciones de vías urinarias en gestantes del hospital gineco-obstétrico ángela loayza de ollague (2016-2017) - Aguilar Abarca, Pamela Andrea (2017)
Urinary tract infections worldwide are a major health problem, especially in pregnant women, causing changes ranging from mild to severe during pregnancy. Urinary tract infections are characterized by the invasion of pathogens in the urinary tract, this infection can be complicated when the bacteria ascends to the kidney causing a pyelonephritis or a descent and arrive to colonize in the low zone where the Bladder, causing cystitis. In pregnancy, the urinary tract infection is more frequent, due to the constant changes that occur during gestation, so that as the embryo advances, the uterus enlarges and causes a collision with the urethra. Prevent proper emptying of the bladder when urinating. Objective: To establish the prevalence and pathogenic agents associated with urinary tract infections in pregnant women attending an outpatient clinic at the Obstetrics and Gynecology Hospital Angela Loayza de Ollague. Materials and methods: It is an experimental study with a quantitative approach. The sample consisted of pregnant women ranging from 14 to 42 years of age to establish the prevalence and causal agents of urinary tract infections during pregnancy. A physical-chemical, microscopic and microbiological analysis of urine was performed. Statistical analysis was performed using the IBM SPSS Statistics Version 23.0 (Statistical Product and Service Solutions for Windows) software, according to the descriptive technique with a 95% confidence and EPI INFO ™ software version 7.2.1. Results: By means of the analysis of the results, it was possible to establish a prevalence of urinary tract infections of 152.54 per 1000 pregnant women; this was in front of the sample of 144 and universe of 944. In relation to the infection, an asymptomatic bacteriuria of 67.4% (97), pyelonephritis 27.0% (39), cystitis 6.0% (8). Most of the urban sector was 74.3% (107), rural 13.9% (20) and 11.8% (17) to other cantons. The most exposed age group is 20 to 25 years. In the interaction of the variables age and type of infection, a higher prevalence of 20 to 25 years was obtained, presenting asymptomatic bacteriuria 71.2% (37), pyelonephritis 23.1% (12), cystitis 6.8% (3). Crossing the variables of place of residence and type of infection shows that most of the urban area presents asymptomatic bacteriuria 75.7% (81), pyoneonephritis 22.4% (24), and cystitis 1.9% (3). In the third and second trimester of gestation, the infection with 47.9% and 37.5%, respectively, occurs more frequently, during which periods maternal-fetal complications may occur; Preterm delivery 95.7% (46) related to asymptomatic bacteriuria, 4.3% (2) pyelonephritis. The causal agent consisted of E. coli 46.7%, Klebsiella pneumoniae 23.3%, Staphylococcus epidermidis 13.3%, Streptococcus viridans 10.0%, Staphylococcus saprophytic 3.33% and Enterobacter aerogenes 3.33%. The attack rate of bacteria was 52.63 and a relative risk for complications was 6.33%. Conclusion: The prevalence of infections in the urinary tract and in turn the most frequent causal agent was determined; the possible maternal-fetal complications that occur because of urinary tract infections, their relative risk, and the agent's attack rate.